Estimation of rotor mast moments using a data-driven observer tuning - Wartmann, J.; Doring, F.A.; Seher-Weiss, S. (My University, 2021)
Incorporating main rotor-states like the tip-path-plane flapping angles into the flight control system of a rotorcraft allows for enhanced handling and ride qualities as well as reduced pilot workload. Still, measuring rotor-states in the rotating frame is cost-intensive and more complex than fixed-frame measurements. In this paper, an observer is proposed to estimate the rotor mast bending moments using only fixed-frame measurements. Therefore, linear models of the research rotorcraft ACT/FHS are identified from an extensive flight test campaign. On this basis, different linear observers are designed and optimized using flight data. Two promising observers of different complexity are then selected using a cross-validation. Finally, these observers are analyzed in the time and frequency domain using a variety of different flight maneuvers like sweeps, stable forward flight and flight in turbulence